2017
DOI: 10.7554/elife.24284
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of the human mutation spectrum

Abstract: DNA is a remarkably precise medium for copying and storing biological information. This high fidelity results from the action of hundreds of genes involved in replication, proofreading, and damage repair. Evolutionary theory suggests that in such a system, selection has limited ability to remove genetic variants that change mutation rates by small amounts or in specific sequence contexts. Consistent with this, using SNV variation as a proxy for mutational input, we report here that mutational spectra differ su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
246
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(285 citation statements)
references
References 40 publications
38
246
1
Order By: Relevance
“…55 When not accounting for ancestry, the mutational differences identified across cancers might be ascribed exclusively to differences in tumor type (for example, kidney cancer vs ovarian cancer), whereas our results demonstrate that these differences may be significantly influenced by ancestry (ie, European vs East Asian). Furthermore, these differences agree with recent findings of mutational differences across ancestry, 56,57 and extend such mutational work into a cancer genome context. However, it is important to note that calling somatic mutations is notoriously difficult, and that even though COSMIC somatic calls represent one of the best curated sets to date, somatic mutation call sets are often plagued by high falsepositive rates.…”
Section: Discussionsupporting
confidence: 90%
“…55 When not accounting for ancestry, the mutational differences identified across cancers might be ascribed exclusively to differences in tumor type (for example, kidney cancer vs ovarian cancer), whereas our results demonstrate that these differences may be significantly influenced by ancestry (ie, European vs East Asian). Furthermore, these differences agree with recent findings of mutational differences across ancestry, 56,57 and extend such mutational work into a cancer genome context. However, it is important to note that calling somatic mutations is notoriously difficult, and that even though COSMIC somatic calls represent one of the best curated sets to date, somatic mutation call sets are often plagued by high falsepositive rates.…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, we note that a number of recent studies have shown that the mutation spectrum changes slightly across populations (3,(82)(83)(84). These findings have largely been attributed to biochemical modifiers of mutation that alter the relative rates of different mutation types by influencing the biochemical process of error/repair over time.…”
Section: Discussionmentioning
confidence: 67%
“…Another important innovation of TrackSig is the used of CCF as a surrogate for evolutionary timing. Similar ideas have been used in human population genetics, where variant allele frequency to get relative order of mutations along the ancestral lineage 25 . In population genetics, allele frequency is calculated across individuals, while we calculate VAF across cell population within a single sample.…”
Section: Relationship To Previous Workmentioning
confidence: 95%